Retreatment of the lower premolar in a single session - Hybridization of the Prodesign Logic RT system and Lima Solla Collors. - Coelho Travassos, Rosana Maria (2024)
The objective of this was to describe a clinical case of endodontic retreatment in a single session in a tooth with chronic apical periodontitis. After anesthesia and absolute isolation with a rubber dam, the coronary opening was made, the obturator material was removed, the Prodesign Logic RT® 25.08 file was made, the working length was determined with an apical locator, and the foraminal patency was made with the Solla Collors Glidepath File 16/02, one millimeter beyond the exit of the apical foramen. The canal was reprepared using Solla Collors 70.03 files. The root canal system is filled using the single cone technique associated with Bio C Sealer cement.  Clinical and radiographic follow-up was carried out 6 months after the canal filling, showing repair of the periapical bone radiolucency. It is concluded that the hybridization of the Prodesign Logic RT system with Lima Solla Collors determined the success of endodontic retreatment.